2015
DOI: 10.1186/s12862-015-0540-9
|View full text |Cite
|
Sign up to set email alerts
|

Bilobate leaves of Bauhinia (Leguminosae, Caesalpinioideae, Cercideae) from the middle Miocene of Fujian Province, southeastern China and their biogeographic implications

Abstract: BackgroundMorphological and molecular phylogenetic studies suggest that the pantropical genus Bauhinia L. s.l. (Bauhiniinae, Cercideae, Leguminosae) is paraphyletic and may as well be subdivided into nine genera, including Bauhinia L. s.s. and its allies. Their leaves are usually characteristic bilobate and are thus easily recognized in the fossil record. This provides the opportunity to understand the early evolution, diversification, and biogeographic history of orchid trees from an historical perspective un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 61 publications
1
16
0
Order By: Relevance
“…Our results suggest extinction of stem-relatives of these two subfamilies, most likely related to Late Eocene and Oligocene cooling, and subsequent diversification of the crown groups during the Oligocene and Miocene, when both groups become diverse at several fossil sites (e.g. Wang et al, 2014;Lin et al, 2015;Poinar, 1991;Poinar and Brown, 2002).…”
Section: Implications For Our Understanding Of the Evolution Of Legummentioning
confidence: 84%
“…Our results suggest extinction of stem-relatives of these two subfamilies, most likely related to Late Eocene and Oligocene cooling, and subsequent diversification of the crown groups during the Oligocene and Miocene, when both groups become diverse at several fossil sites (e.g. Wang et al, 2014;Lin et al, 2015;Poinar, 1991;Poinar and Brown, 2002).…”
Section: Implications For Our Understanding Of the Evolution Of Legummentioning
confidence: 84%
“…Some studies of Fotan flora (Jacques et al, ; Lin et al, ; Shi et al, ; Shi & Li, ; Wang et al, ) supported a similar conclusion. The Garcinia leaves were found in a forest assemblage dominated by angiosperms, including species belonging to the families Dipterocarpaceae, Leguminosae, Moraceae, Urticaceae, and Euphorbiaceae, which have a high diversity in tropical to warm subtropical zones (Jacques et al, ; Lin et al, ; Shi et al, ; Shi & Li, ; Wang, Sun, Jin, Deng, et al, ). Combined with the Fagaceae and Lauraceae fossils, this finding indicates that the Zhangpu area should have had a warm and humid, tropical to subtropical climate during the depositional period of the Fotan flora.…”
Section: Discussionmentioning
confidence: 79%
“…Taking the ecological preference of G. tonkinensis into consideration, we can infer that G. zhangpuensis lived in a warm and humid tropical to subtropical and monsoonal climate, with a higher annual average temperature than the current temperature of Fujian. (Jacques et al, 2015;Lin et al, 2015;Shi et al, 2014;Shi & Li, 2010;. Combined with the Fagaceae and Lauraceae fossils, this finding indicates that the Zhangpu area should have had a warm and humid, tropical to subtropical climate during the depositional period of the Fotan flora.…”
Section: Palaeoenvironmental Interpretationsmentioning
confidence: 85%
“…Also, leaf lobes were noted to be essential to discriminate specific vein patterns and can display accurate homological and/or ancestral relationships (Viscosi and Cardini 2011;Inamdar and Shenoy 1982). Lobation and primary vein size were also some of the leaf characters served as basis for classifying the bilobate leaf fossils and evaluating the fossil record and biogeography of Bauhinia species (Lin et al 2015). It was observed that accessions with irregular secondary vein spacing were unlobed while those that have secondary vein spacing increasing towards the base were palmately lobed.…”
Section: Resultsmentioning
confidence: 99%